SCHOOL LITERACY MOVEMENT AND IMPACT ON STUDENTS' READING INTEREST ELEMENTARY SCHOOL - Yuyun Elizabeth, Karmilasari, Siti Ema Iklimah, Netty Herawati (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2023)
This research was conducted to find out a new way of implementing the School Literacy Movement program that can increase elementary school students' interest in reading. This study uses a literature study that reviews 6 journals that are relevant to the research topic. This research with a quantitative approach was carried out by looking for references from relevant and similar journals to analyze the data taken from the Google schoolar website. Journals are collected for analysis and data comparison. From this research, finding a new way of the school literacy movement to increase reading interest is procuring reading books in schools that should be updated according to the times, educators who innovate, Increasing Educators' Competence, Adding book collections in libraries, Utilizing Reading Corners and To increase reading interest needs to be supported by all parties. From the results of the analysis it was concluded that the impact of the school literacy movement can increase reading interest and the results of this study can be recommended for the school literacy movement to increase students' interest in readin.